17 | The empirical use of antibiotics in hospital and territorial settings: guidelines from a Provincial Health Authority in Calabria as a tool for antimicrobial stewarship - I. Lazzaro; M. Cannataro; S. A. Mirarchi (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2026)
Background. Antimicrobial stewardship implements initiatives to promote the appropriate and informed use of antibiotics, including in cases of empirical therapy, to fight multidrug-resistant pathogens. The Medical Directorate of a Provincial Health Authority in Calabria in operational collaboration with the Pharmaceutical Area, issues corporate guidelines on the empirical use of antibiotics combining hospital protocols based on microbial epidemiology (DCA N. 72/2020, Calabria Region) with territorial protocols for primary care, using the World Health Organization’s AWaRe classification. The aim of this work is to draft a joint hospital- territory document as a tool to fight antibiotic resistance. Materials and Methods. The analysis is conducted by consulting documents from the Calabria Region related to the PNCAR (DCA n. 72/2020 - n. 137/2021 - n. 275/2025, Decree n. 7017/2025); ISS Surveillance Reports 2024; AIFA Antibiotics Report 2023; WHO AWaRe Manual. A review of therapy manuals and scientific evidence is then carried out2. Results. In the drafted document, empirical antibiotic uses —which can be used in selected cases—are reported in tables organized by type of infection, dosage, administration schedule and duration of treatment for both hospital and territorial settings. It was decided to use the standard AWaRe color-coded alert system to highlight Access (green), Watch (orange), and Reserve (red) antibiotics, thus increasing clinical and prescribing awareness1. In Calabria, antibiotic use in the Access category is estimated to be below the European target (≥65%), and the use of Watch antibiotics exceeds 50%. This is combined with local microbial epidemiology data, which indicate a growth in bacterial resistance. Conclusions. While Access may be the first-line treatment option, Watch antibiotics should be used with greater caution in severe clinical conditions. This document serves as a guide for healthcare professionals to prescribe the right medication to the right patient, even in cases of empirical treatment, thus helping to fight antibiotic resistance.